An emerging class of hyperbolic lattice exhibiting tunable elastic properties and impact absorption through chiral twisting. (October 2020) - Meng, Liang; Shi, Jianxiong; Yang, Chen; Gao, Tong; Hou, Yuliang; Song, Longlong; Gu, Dongdong; Zhu, Jihong; Breitkopf, Piotr; Zhang, Weihong
Abstract: Lightweight lattice structures and chiral metamaterials have both received extensive attention during the past decades. This work builds up a systematic design procedure for an emerging class of architected materials, achieving chirality and achirality under the same framework of parameterization. The design of the so-called 'hyperbolic unit cell' takes inspiration ultimately from the double-layered morphology of the fore-wing shells of flying beetles, being intended to replicate the hyperbolic geometric feature. The tessellation schemes that populate the microstructure to a component level are stirred up by the similarity with Euclidean tiling of convex regular polygons. Numerical and experimental studies revealed a wide variation of elastic constants for hyperbolic materials maintaining the same volume fraction, making more visible their applications under various loading scenarios, including compression, tension and shear. Also, a significant twisting effect, observed on the chiral cellular material, is shown to be advantageous in the design of buffering plates and energy-absorbing devices.